2012
DOI: 10.1016/j.dcn.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The development of the error-related negativity (ERN) and its relationship with anxiety: Evidence from 8 to 13 year-olds

Abstract: Because anxiety disorders appear to follow developmental trajectories that begin early in development, it may be useful to examine the neurodevelopmental correlates of specific cognitive processes that have been linked to anxiety. For instance, the error-related negativity (ERN) is a negative deflection in the event-related potential that is maximal approximately 50 ms following the commission of errors at fronto-central electrode sites, and has consistently been found to be more negative among anxious adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
169
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(189 citation statements)
references
References 64 publications
19
169
1
Order By: Relevance
“…Of importance, however, recent work suggests that the association between the ERN and internalizing may change across development. Specifically, Meyer, Weinberg, Klein, and Hajcak (2012) demonstrated, as in adults, enhanced ERN for anxious versus nonanxious older children (11-13 years), whereas somewhat smaller ERN was evident for anxious versus nonanxious younger children (8-10 years). In a recent follow-up study (Torpey et al, 2013), this research group showed that children even younger in age (6 years) characterized as highly fearful showed reduced ERN in comparison with typically developing less fearful peers.…”
Section: Clinical Feasibility Of Measuring Neurobehavioral Constructsmentioning
confidence: 76%
“…Of importance, however, recent work suggests that the association between the ERN and internalizing may change across development. Specifically, Meyer, Weinberg, Klein, and Hajcak (2012) demonstrated, as in adults, enhanced ERN for anxious versus nonanxious older children (11-13 years), whereas somewhat smaller ERN was evident for anxious versus nonanxious younger children (8-10 years). In a recent follow-up study (Torpey et al, 2013), this research group showed that children even younger in age (6 years) characterized as highly fearful showed reduced ERN in comparison with typically developing less fearful peers.…”
Section: Clinical Feasibility Of Measuring Neurobehavioral Constructsmentioning
confidence: 76%
“…Importantly, the ERN can be elicited in children as young as 6 (Torpey, Hajcak, Kim, Kujawa, & Klein, 2012), if not younger. In a recent paper, we examined the relationship between ERN and anxiety as a function of age among 8-to 13-year-olds (Meyer, Weinberg, Klein, & Hajcak, 2012). We found that the relationship between ERN and anxiety was strongly moderated by age: Increased ERN was related to anxious symptoms, but only among older (i.e., 11-to 13-year-old) children.…”
Section: Development Of the Ern And Trajectories Of Riskmentioning
confidence: 94%
“…Individual variation in ERN magnitude is thought to index differences in sensitivity to error commission and defensive reactivity following mistakes (Hajcak, 2012; Weinberg, Riesel, & Hajcak, 2012). In keeping with the view that individuals with internalizing and externalizing tendencies have increased and decreased sensitivity to potential threat, respectively, studies have consistently found an increased ERN among internalizing individuals and a decreased ERN among externalizing individuals For example, work in adults and children suggests that the ERN magnitude is increased in individuals characterized by internalizing disorders or traits, such as obsessive-compulsive disorder (OCD; Carrasco et al, 2013; Endrass, Klawohn, Schuster, & Kathmann, 2008; Endrass et al, 2010; Gehring, Himle, & Nisenson, 2000; Hajcak, Franklin, Foa, & Simons, 2008; Riesel, Endrass, Kaufmann, & Kathmann, 2011; Ruchsow, Grön, et al, 2005), depression (Chiu & Deldin, 2007; Holmes & Pizzagalli, 2008, 2010; however, see: Olvet, Klein, & Hajcak, 2010; Weinberg, Klein, & Hajcak, 2012), generalized anxiety disorder (Weinberg, Olvet, & Hajcak, 2010; Xiao et al, 2011), heterogeneous anxiety disorders (Ladouceur, Dahl, Birmaher, Axelson, & Ryan, 2006; Meyer et al, 2013), OCD traits (Gründler, Cavanagh, Figueroa, Frank, & Allen, 2009; Hajcak & Simons, 2002; Santesso, Segalowitz, & Schmidt, 2006), trait anxiety (Meyer, Weinberg, Klein, & Hajcak, 2012; Pourtois et al, 2010), negative affect (Bush, Luu, & Posner, 2000; Hajcak, McDonald, & Simons, 2004), and behavioral inhibition (Amodio, Master, Yee, & Taylor, 2008; Boksem, Tops, Wester, Meijman, & Lorist, 2006; McDermott et al, 2009). In contrast, the ERN tends to be diminished in individuals characterized by externalizing disorders or traits, such as substance abuse (Franken, van Strien, Franzek, & van de Wetering, 2007; Luijten et al, 2014; Marhe, van de Wetering, & Franken, 2013), attention deficit hyperactivity disorder (ADHD; Albrecht et al, 2008; Groen et al, 2008; Hermann, Ziegler, Birbaumer, & Flor, 2002), psychopathy (Munro et al, 2007; Von Borries et al, 2010), trait impulsivity (Potts, George, Martin, & Barratt, 2006; Ruchsow, Spitzer, Grön, Grothe, & Kiefer, 2005), disinhibitory personality traits (Dikman & Allen, 2000), and externalizing traits (Hall, Bernat, & Patrick, 2007).…”
mentioning
confidence: 99%